(-2x^2+3y^3)+(6x-5)=0

Simple and best practice solution for (-2x^2+3y^3)+(6x-5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-2x^2+3y^3)+(6x-5)=0 equation:


Simplifying
(-2x2 + 3y3) + (6x + -5) = 0

Remove parenthesis around (-2x2 + 3y3)
-2x2 + 3y3 + (6x + -5) = 0

Reorder the terms:
-2x2 + 3y3 + (-5 + 6x) = 0

Remove parenthesis around (-5 + 6x)
-2x2 + 3y3 + -5 + 6x = 0

Reorder the terms:
-5 + 6x + -2x2 + 3y3 = 0

Solving
-5 + 6x + -2x2 + 3y3 = 0

Solving for variable 'x'.

The solution to this equation could not be determined.

You can always share this solution

See similar equations:

| 2x^2+6x+4=0 | | 2x^2-5x-75=0 | | 2x^2-10x+18=0 | | 9s^2+3s-20=x | | (x-1)(x^2-4)+2(x-1)(x+2)=(x-1)P | | 9x^2-4.5x-3.5=0 | | 6x^2-5x-14=0 | | x^4-7x-18=0 | | x^2-8x+18=0 | | x^2-8b+18=0 | | 30a^2+am-m^2=0 | | 30a^2+am-m^2=o | | 12s^2+11st-5t^2=0 | | 14x^2+11yx-15y^2=0 | | 3x^2+8=0 | | -2v^2-v+12=-3v^2+6v | | x^2+15x-64=0 | | 2x^2+8x-2=0 | | 12x^2-x-20=0 | | 5x^2+13x+6=0 | | x^3-12x^2+35x=0 | | x^3-13x^2+30x=0 | | 6x^2+17x-45=0 | | x^4-3x^2+1=0 | | 5x^2-5x-3= | | 3x^2-13x+14=0 | | 6x^2+x-c=(cx-1)(3x+2) | | X*x=x^2 | | 9c=c^2 | | 3x^2-12=0 | | 3x^2-8=0 | | x^2+6=6x^2-16 |

Equations solver categories